2017
DOI: 10.4132/jptm.2016.07.01
|View full text |Cite
|
Sign up to set email alerts
|

A Pyloric Gland-Phenotype Ovarian Mucinous Tumor Resembling Lobular Endocervical Glandular Hyperplasia in a Patient with Peutz-Jeghers Syndrome

Abstract: We describe an ovarian mucinous neoplasm that histologically resembles lobular endocervical glandular hyperplasia (LEGH) containing pyloric gland type mucin in a patient with Peutz-Jeghers syndrome (PJS). Although ovarian mucinous tumors rarely occur in PJS patients, their pyloric gland phenotype has not been clearly determined. The histopathologic features of the ovarian mucinous tumor were reminiscent of LEGH. The cytoplasmic mucin was stained with periodic acid-Schiff reaction after diastase treatment but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 5 publications
(6 reference statements)
0
14
1
Order By: Relevance
“…In fact, most publications on mucinous change in the Fallopian tubes are related to patients with Peutz-Jeghers syndrome as in the case of our patient and her daughter. 8 In our case, we did not find evidence of a precursor lesion of cervical or uterine origin . The fact that the patient had mucinous metaplasia in both Fallopian tubes supported the tubal origin of the tumor.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In fact, most publications on mucinous change in the Fallopian tubes are related to patients with Peutz-Jeghers syndrome as in the case of our patient and her daughter. 8 In our case, we did not find evidence of a precursor lesion of cervical or uterine origin . The fact that the patient had mucinous metaplasia in both Fallopian tubes supported the tubal origin of the tumor.…”
Section: Discussioncontrasting
confidence: 61%
“…We have only found mention of four mucinous cystadenomas, one borderline mucinous tumor and two cases of an ovarian mucinous tumor with gastric differentiation that respectively resembled endocervical glandular hyperplasia and adenoma. 2,4,810…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Recently, an ovarian mucinous tumour resembling LEGH and with a pyloric gland immunophenotype has been described in a patient with PJS and the authors suggested that STK11 mutation may play a role in the development of pyloric-type mucinous lesions at various anatomical locations. 57 One of us (WGM) has seen a similar ovarian mucinous neoplasm admixed with a SCTAT in a patient with PJS. There are currently no recommended gynaecological screening or clinical surveillance guidelines for PJS patients.…”
Section: Peutz-jeghers Syndrome (Pjs)mentioning
confidence: 99%
“…All these lesions and the patient's multiple hamartomatous polyps in the jejunum showed a pyloric phenotype, 33 supporting the proposed association of STK11 mutation with multifocal mucinous proliferations of pyloric type. 57 Although multiple mucinous lesions in the female genital tract are postulated to represent synchronous independent proliferations, in some cases it may be difficult to distinguish between synchronous and metastatic lesions. For example in a patient with a morphologically well differentiated cervical GAS and a bland ovarian mucinous neoplasm, it may be difficult or impossible to determine whether the ovarian lesion is a primary neoplasm or a bland metastasis.…”
Section: Peutz-jeghers Syndrome (Pjs)mentioning
confidence: 99%